The Effectiveness of Accelerating Halal Product Certification: Regulations and Companions - Rofi'ah, Khusniati; Safira, Martha Eri; Rosele , Muhammad Ikhlas (Lembaga Contrarius Indonesia, 2024)
A variety of regulations have regulated halal certification policies. However, the implementation of accelerated halal certification regulations in Indonesia has not been effective because there still needs to be improvement in substance, structure, and legal culture. This research aims to analyze the effectiveness of accelerating halal certification between Indonesia and Malaysia. This socio-legal research uses a comparative approach with Malaysia. The data used are primary and secondary interviews, surveys, case studies, and literature studies. The research results show that, first, that the effectiveness of halal product regulations in Indonesia has yet to be maximized in terms of substance, structure, and legal culture. Second, the regulatory and companion factors required for halal certification are strategies to accelerate halal certification in Indonesia. The government must promptly enhance regulations regarding halal products, supervise law enforcement, and conduct outreach and education initiatives for the public in response to the numerous challenges encountered in expediting halal product certification. This research will impact accelerating certification, which can increase economic growth and serve as a legal basis for formulating the adoption of Indonesian government regulations.